The correlation between Pax5 deletion and patients survival in Iranian children with precursor B-cell acute lymphocytic leukemia - Moafi, A.; Zojaji, A.; Salehi, R.; Najafi Dorcheh, S.; Rahgozar, S. (Cellular and Molecular Biology, 2017)
Despite advances in treatment, children with acute lymphoblastic leukemia (ALL) still experience drug resistance and relapse. Several gene mutations are involved in the onset of this disease and resistance to therapy. The present study examines the incidence of IKZF1, CDKN2A/B, PAX5, EBF1, ETV6, BTG1, RB1, JAK2, and Xp22.33 gene deletions/duplications associated with pediatric ALL in Iran and investigates the possible effect of these mutations on drug resistance. Three-year disease-free survival (3DFS) was evaluated for children diagnosed with Philadelphia negative precursor-B-cell ALL hospitalized at Sayed-al-Shohada Hospital, Isfahan-Iran, from January 2009 until December 2012. DNA was extracted from bone marrow slides, and ALL correlated gene deletions and duplications were measured using Multiplex Ligation-dependent Probe Amplification (MLPA) method. The correlation between gene mutations and 3DFS was then assessed. Among the nine aforementioned investigated genes, 63% of samples showed at least one gene mutation. At least two concomitant genomic mutations were observed in 42% of samples. Pax5 deletion was the most prevalent gene mutation observed in 45% of cases, and showed significant negative impact on response to treatment. CDKN2A/B (9p21.3) gene deletion, and ETV6 (12p13.2) gene duplication also demonstrated negative effect on patient survival and contributed to a worse prognosis if concomitant with Pax5 gene deletion. ALL patients with one of the gene deletions including Pax5 and CDKN2A/B (9p21.3) or ETV6 (12p13.2) gene duplication are classified as high-risk patients and need more intensified protocols of treatment to improve their chance of survival.